The Management of a Pregnant with Aplastic Anemia: A Case Report - Sakar, Mehmet Nafi; Atay, Ahmet Engin; Gul, Talip (Fırat University, 2012)
Pregnancy is rarely observed in patients with aplastic anemia. Anemia, hemorrhage and infection may complicate pregnant with aplastic anemia and generally leads to growth restriction, premature labor and intrauterine fetal death. Twenty eight-year-old patient; gravidity 3, parity 2 and 1 alive, was pregnant for 29 weeks and had a history of aplastic anemia. Biochemical analysis and obstetric ultrasonographic examinations were performed during the regular visits. Our patient experienced preterm delivery. Due to late arrival for tocolysis, normal vaginal delivery was performed. Supportive therapy may diminish the rate of maternal and fetal complicatons. It is essential to inform patient and relatives about regular visits and earlier admittance at the time of emergency for minimizing life-threating risks.

Aplastik anemi ve gebelik birlikteliği ender görülür. Annede anemi, kanama ve enfeksiyon görülebilirken, fetüste gelişme kısıtlılığı, erken doğum, intrauterin ölüm izlenebilir. Yirmisekiz yaşında, gravidite 3, parite 2 ve yaşayanı 1 olan hastanın, aplastik anemi tanısı ile 29 haftalık gebeliği mevcuttu. Hastaya belirli aralıklarla obstetrik ultrason ve hemogram bakıldı. Doğum sancılarının olması üzerine başvuran hasta, tokoliz için geç kalındığından erken doğum yaptı. Destek tedavisi maternal ve fetal komplikasyon oranını düşürebilir. Hastalar olası komplikasyonlar hakkında bilgilendirilmeli, kontrolleri düzenli yapmaları önemle belirtilmelidir. Acil bir durumda erken başvuru yapılması ile hayati komplikasyonlar azaltılabilecektir.
Aplastik Anemili Gebenin Yönetimi: Olgu Sunumu